GNSS radio occultation technique for atmospheric refractivity profiling and planetary boundary layer height detection - Han, Bo (2018)
Global Navigation Satellite System (GNSS) Radio Occultation (RO) is an atmospheric remote sensing method attracting extensive attention with increasing number of RO missions. Valuable atmospheric parameters can be detected using this technique, providing crucial additions to current weather and climate studies. GNSS RO data have been assimilated into various weather data and models. During a RO event, the GNSS signals grazing the Earth’s atmosphere are delayed and bent before picked up by the GNSS receivers. The excess Doppler frequency information measured by the receivers contains the Earth’s atmospheric effect and is used to invert to atmospheric parameters such as refractivity profiles. This thesis covers several aspects in GNSS RO study. The GNSS tracking algorithms are first described which lays the groundwork for GNSS RO. Then, we study the RO inversion algorithms using the tracked GNSS signals to obtain the atmospheric refractivity profiles, and the error characteristics of the orbital errors’ effect on the retrieved refractivity errors. Finally, the GNSS RO’s application is extended to planetary boundary layer height (PBLH) detection. The tracking algorithm in the thesis focuses on the open loop (OL) tracking algorithm which can track the GNSS signals to a lower altitude compared to the common closed loop (CL) algorithm. The OL algorithm is applied to the raw GPS data collected during a mountain-based RO (MRO) experiment. The RO inversion algorithms for both space-based and ground-based RO is described. For the space-based RO, the Radio Occultation Processing Package (ROPP) provides more detailed inversion algorithms. The performance of ROPP is statistically evaluated for the Southeast Asia region by comparing with the co-located Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) and European Centre for Medium-Range Weather Forecasts (ECMWF) profiles. The ground-based RO algorithm is applied to the GNSS RO data collected during the MRO experiment. Vertical refractivity profiles below the receiver height near the MRO experiment site are retrieved. The refractivity profiles are further exploited to detect the PBLH using the common refractivity gradient method. An obvious GNSS signal amplitude drop-and-rise-back pattern is constantly observed in the collected data. Using the MRO geometry and the time when the GNSS signal’s amplitude drops to the lowest, the PBLH can be directly detected using the signal’s amplitude. This signal amplitude-based method is thus proposed for application on the collected MRO data and statistically verified. This method shows advantages such as easy to implement and avoids some of the assumptions and steps associated with the popular refractivity gradient-based method.